ANALYTIC MODEL OF STOCHASTIC PROCESS OF DAMAGE DEVELOPMENT IN SOLID BODY DURING UNIFORM TENSION - Martynyuk P.A. (My University, 2001)
Real rock is non-uniform solid body. Non-uniformity of the rock is determined by presence of pores, microcracks etc. Recurrence formulae have been offered for probabilities, describing simulation model of kinetic process of arising and combining the microcracks during modeling the destruction of uniformly stretched plane volume. It has been shown that use of these formulae makes it possible to determine influence of the main parameters of the model on damage development. In this case, various laws of varying the radius of region of the interacting microcrack capture can be. The microcracks are formed under action of stress.